COMPARATIVE ANALYSIS OF TASK-BASED AND PROJECT-BASED LEARNING - Maftuna Abdurasulova (TADQIQOTLAR.UZ, 2024)
This study provides a comparative analysis of Task-Based Learning (TBL) and Project-Based Learning (PBL) in language education. Both approaches prioritize active, student-centered learning, yet they differ in structure, implementation, and outcomes. Through a mixed-methods approach involving surveys, interviews, and classroom observations, the study explores how TBL and PBL impact student engagement, language proficiency, and critical thinking skills. The findings highlight the strengths and challenges of each approach, offering insights for educators to optimize their instructional strategies.